Hypertension: from basic research to clinical practice - Islam, Md. Shahidul (Advances in Experimental Medicine and Biology, 2017)
Hypertension: from basic research to clinical practice" contains a unique collection of selected chapters written by experts and enthusiasts engaged in research and treatment of hypertension, a condition that affects around a billion people in the world. The chapters describe fundamental researches at cellular and molecular levels to the science, and art of treatment of the condition in clinical practice. The topics included ranges from pathophysiology of hypertension, through monitoring of hypertension, to the treatment of hypertension in different patient categories. It contains essential background information as well as cutting edge research, and state of the art treatment alternatives in this broad field. From the beginners, and research students to the expert clinicians, and established scientists, everybody has something to learn from this book. .